J. E. Tatengkeng and Robert Frost’s Poems: An Application of Michael Riffaterre’s Semiotic Model - Karmila Mokoginta; Nur Ilmi; Hartina Mahardhika (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2021)
This paper describes the results of poem analysis using the semiotic model of Riffaterre. The objects of analysis were poems written by J.E Tatengkeng from Indonesia including Di Lereng Gunung, Bulan Terang, and Melati; and Robert Frost from America including Nothing Gold Can Stay, Fireflies in the Garden, and After Apple Picking. The analysis was conducted using two steps of reading. The first was the heuristic reading conducted by using linguistic knowledge; while the second was the retroactive reading conducted by using knowledge beyond the text. This second step was intended to conclude the hypograms, and based on the hypograms, matrices and significance of the poems were concluded. The analysis revealed the poems’ matrices and significance related to the value of love, beauty of nature, and religious belief. Keywords: Riffaterre, J.E. Tatengkeng, Robert Frost.